2013
DOI: 10.1039/c3ra45541f
|View full text |Cite
|
Sign up to set email alerts
|

RAFT polymerization of fatty acid containing monomers: controlled synthesis of polymers from renewable resources

Abstract: The incorporation of bio-renewable resources such as fatty acids into the polymer chain allows tailoring the properties of products, for their widespread applications. A series of methacrylate monomers with sidechain fatty acids (FAMA) were synthesized by esterification of 2-hydroxyethyl methacrylate (HEMA) and fatty acids, such as caprylic, capric, lauric, mysritic, palmitic and stearic acid. Consequent polymerization of FAMAs via reversible addition-fragmentation chain transfer (RAFT) gave side-chain fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 36 publications
1
58
0
Order By: Relevance
“…By comparing the T g values of unsaturated polymers to those of saturated polymers, the hydrogenation of polymers led to slightly higher T g values. However, because of the presence of longer linear alkyl side chains, the polymers with the branches of 12 or 16 carbon atoms started to crystallize with the lower T m values, which was in good agreement with other polymers bearing the saturated fatty acid‐derived side chains . As a result, the T m values at −30.6 and 10.6 °C were observed for the unsaturated polymers P3 and P4 , respectively.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…By comparing the T g values of unsaturated polymers to those of saturated polymers, the hydrogenation of polymers led to slightly higher T g values. However, because of the presence of longer linear alkyl side chains, the polymers with the branches of 12 or 16 carbon atoms started to crystallize with the lower T m values, which was in good agreement with other polymers bearing the saturated fatty acid‐derived side chains . As a result, the T m values at −30.6 and 10.6 °C were observed for the unsaturated polymers P3 and P4 , respectively.…”
Section: Resultssupporting
confidence: 78%
“…As a result, the T m values at −30.6 and 10.6 °C were observed for the unsaturated polymers P3 and P4 , respectively. As the chain length of pendant linear branches increased, the crystallization of side chains might be enhanced, leading to the higher T m values and crystallinity of polymers . After the saturation of the backbone, the T m values for the saturated polymers HP3 and HP4 increased slightly, and there were two endothermic peaks observed for HP3 (–32.8 and −4.9 °C) and a shoulder peak alongside for HP4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2,2′‐azobisisobutyronitrile (AIBN, 98%, Sigma) was recrystallized from methanol and BzMA (96%, Sigma) was passed through a basic alumina column to remove inhibitors/anti‐oxidants. 4‐Cyano‐4‐(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid (CDP) and oleic acid based methacrylate monomer 2‐(methacryloyloxy)ethyl oleate (MAEO) were synthesized as described elsewhere. The solvents such as hexanes (mixtures of isomers), n ‐heptane, methanol (MeOH), acetone, ethyl acetate, tetrahydrofuran (THF), dichloromethane (DCM), and so forth were purified by standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Maiti et al reported the incorporation of homopolymers with fatty acid pendants to block copolymers via Reversible Addition Fragmentation Chain Transfer polymerization (RAFT). These monomers displayed crystalline behavior dependent on the size of the fatty acids (25).…”
Section: Table 1 Common Fatty Acids Found In Common Vegetable Oilsmentioning
confidence: 99%